Media Flashcard dalam Pembelajaran Kosakata Bahasa Inggris di SDN Cibitung 2 Cibokor Kabupaten Cianjur - Saepuloh, Asep; Ningsih, Dinni Nurfajrin; Sungkawa, Muhamad Guntur Gaos; Diningsih, Cinde Adia; Zuber (LPPM UNINUS, 2024)
This Community Service was integrated with the implementation of the KKN program of Suryakancana University in 2023, and there were several differences with the implementation of the previous community programs. This year, students are projected to do community service in the area closest to their houses, with their own work program. This Community Service aims to reintroduce English through learning English vocabulary, especially at the elementary school level, in the fifth grade, with jobs and professional material, at the public elementary school Cibitung 2 Cibokor, using flashcard media. This service involved 5 lecturers and 9 students as the team. It is hoped that this community service can make a significant contribution to improving the quality of English language learning at the elementary school level, especially at SDN Cibitung 2 as well as enriching students' learning experiences in understanding and using new vocabulary. Keywords: English, Flashcard, Learning, Vocabulary